'Discussed, Reformulated and Enriched Many Times': The Supreme Court of Canada's Equality Jurisprudence - Busby, Karen (Social Science Research Network, 2014)
The equality rights guarantee contained in section 15 of the Canadian Charter of Rights and Freedoms has been described by members of the Supreme Court of Canada as “the most difficult right” and “the Charter’s most conceptually difficult provision.” Therefore, it is not surprising that, as Mr. Justice LeBel stated in Québec v A., “the analytical framework [of s. 15] developed by this Court has been discussed, reformulated and enriched many times over the last two decades”. Mr. Justice Cory stated in Vriend that the equality rights guarantee in the Charter embodies “our fondest dreams, the highest hopes and the finest aspirations of Canadian society.” In this paper, I will look back at the last decade of Supreme Court of Canada case law and review how it has been reformulated. I will then look forward and make some comments about where the Court should go with its equality jurisprudence in the next decade if it is to help us realize the “finest dreams of Canadian society.”